Navigating work with generative AI: Knowledge workers' perspective - Korhonen, Maiju (2025)
This master’s thesis examines the phenomenon of knowledge workers using applications that utilize LMMs such as ChatGPT or Copilot. The value this study brings is the gained deeper understanding on how knowledge workers perceive these kinds of applications in their work. The research method chosen for this work is Grounded Theory Method due to its iterative nature and applicability in information systems and flexibility to investigate phenomenon. Knowledge workers from different kinds of fields were interviewed and the material was inspected through open axial and selective coding. The findings from this thesis can be divided into four main categories. Knowledge workers perceive AI applications as unreliable and as tools that can be used in a wide variety of ways. They notice personal development in creating prompts and a sense of collaboration when using these kinds of applications. These findings can all be seen as part of knowledge workers navigating work with generative AI.